Insights into the thermal characteristics and dynamics of stagnant blood conveying titanium oxide, alumina, and silver nanoparticles subject to Lorentz force and internal heating over a curved surface - Li, Shuguang; Li, Yijie; Al Mesfer, Mohammed K.; Ali, Kashif; Jamshed, Wasim; Danish, Mohd; Irshad, Kashif; Ahmad, Sohail; Hassan, Ahmed M. (Nanotechnology reviews (Berlin), 2023)
It is very significant and practical to explore a triple hybrid nanofluid flow across the stuck zone of a stretching/shrinking curved surface with impacts from stuck and Lorentz force factors. The combination (Ag–TiO –Al /blood) hybrid nanofluid is studied herein as it moves across a stagnation zone of a stretching/shrinking surface that curves under the impact of pressure and Lorentz force. Exact unsolvable nonlinear partial differential equations can be transformed into ordinary differential equations that can be solved numerically by similarity transformation. It was discovered that predominant heat transfers and movement characteristics of quaternary hybrid nanofluids are dramatically affected. Numerous data were collected from this study to illustrate how parameters of flow affect the temperature, velocity, heat transmission, and skin friction characteristics. The axial and radial velocities for both fluids (Newtonian and ternary hybrid nanofluid) are increased due to the increasing function of the curvature parameter, magnetic field, and suction parameter. Additionally, the direct relationship between the temperature and heat transfer decreases the heat transfer rate by the curvature parameter, magnetic field, suction parameter, Prandtl number, and heat source/sink. The higher the values of the curvature parameter, the higher the shear stress and velocity.